2010
DOI: 10.2807/ese.15.11.19512-en
|View full text |Cite
|
Sign up to set email alerts
|

A possible foodborne outbreak of hepatitis A in the Netherlands, January-February 2010

Abstract: As of 1 March 2010, a total of 11 primary cases with onset of symptoms between 31 December 2009 and 10 February 2010, have been identified with identical hepatitis A genotype IB strains in the Netherlands. A relation with Australian and French foodborne outbreaks occurring in 2009 and 2010 is suspected. Ten of the 11 primary cases indicated that they had consumed one or more products containing semi-dried tomatoes during their incubation period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Fresh produce has become one of the leading causes of foodborne illnesses in the United States. , High-risk fresh produce such as raw tomatoes have caused several large outbreaks of human salmonellosis over the past few years. In 2010, the Dutch health and food safety authorities issued an update relating to an outbreak of hepatitis A infection associated with semidried tomatoes in oil, which affected 13 people in The Netherlands . Due to the limited efficacy of widely used chlorinated wash water on inactivation of food pathogens for fresh produce, alternatives to chlorine such as natural plant extracts have received much attention in the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…Fresh produce has become one of the leading causes of foodborne illnesses in the United States. , High-risk fresh produce such as raw tomatoes have caused several large outbreaks of human salmonellosis over the past few years. In 2010, the Dutch health and food safety authorities issued an update relating to an outbreak of hepatitis A infection associated with semidried tomatoes in oil, which affected 13 people in The Netherlands . Due to the limited efficacy of widely used chlorinated wash water on inactivation of food pathogens for fresh produce, alternatives to chlorine such as natural plant extracts have received much attention in the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…The studies were conducted over a period from 1983 to 2022. Majority of the studies were from USA (10) [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ], followed by France (3) [ [29] , [30] , [31] ], and other countries [ [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] ]. Continent-wise, North America (17) and Europe (12) reported 88% of all included studies.…”
Section: Resultsmentioning
confidence: 99%
“…They included beverages [ 21 ], fruits (blueberries, apples, pears, frozen pomegranates, frozen berries, blackberries, frozen raspberries, frozen strawberries, mango) [ 22 , 25 , 26 , 32 , [34] , [35] , [36] , [45] , [46] , [47] , 49 , 50 ], vegetables (onion, lettuce & tomatoes) [ 19 , 20 , 29 , 33 , 42 ], dates [ 41 , 51 ], shellfish [ 30 ], scallops [ 27 ], Oysters [ 24 ], baked foods [ 28 ], salads [ 39 ], and ice-creams [ 40 ]. Nine among the 33 studies reported the HAV outbreak linked to an imported food product [ 22 , 26 , 29 , 36 , 41 , 45 , 47 , 50 , 51 ], while 12 of them were indigenous food-related outbreaks [ 21 , 24 , 28 , 30 , 35 , 38 , 39 , [42] , [43] , [44] , 46 ]. The mean age of the patients infected with HAV ranged from 18 to 60 years ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations